Remote sensing of mountain glaciers and ice caps in Iceland - Sigurðsson, Oddur; Williams, Richard S; Martinis, Sandro; Münzer, Ulrich (Springer Praxis Books, 2014)
In 2000, Iceland’s glaciers covered 11,079 km2, or 10.7 % of its contiguous area. There are 269 named glaciers, including 14 ice caps with 109 associated outlet glaciers, 8 ice flow basins, 55 cirque glaciers, 73 mountain glaciers, and 5 valley glaciers. Twentyone surge-type glaciers have been documented. The superposition of ice caps on active volcanoes and associated rift zones within the neovolcanic zones of Iceland produces aperiodic jökulhlaups. Jökulhlaups also result from the failure of ice dams on ice-marginal lakes. In association with Icelandic scientists, airborne thermal infrared surveys of some glaciers were carried out in 1966, and, in 1974, the first analyses of satellite images of glaciers in Iceland were published. Icelandic scientists began radio-echo sounding to determine the thickness of ice caps in 1976. The start of systematic, annual field measurements of the fluctuations of Iceland’s glaciers were begun in 1930; now in the 21st century, between 40 and 50 termini are being measured annually. Systematic instrumental measurements of meteorological variables were started in the 19th century at a few coastal stations, and later expanded to a nationwide network. On September 8, 1972 the first medium resolution satellite images (ERTS-1/Landsat-1) of Iceland’s glaciers were acquired; subsequently, a variety of imaging and nonimaging sensors on different polar-orbiting satellites have provided aperiodic coverage of Iceland’s glaciers. Long-term sets of glaciological data, whether compiled from sequential map series, ground observations (termini fluctuations), and other ground measurements (mass balance studies) or from analyses of data acquired by satellite sensors, such as Landsat MSS, RBV, TM, ETMþ, OLI, Seasat radar, Terra ASTER, and ICESat GLAS, have successfully documented changes in the area and mass balance (volume) of Iceland’s glaciers. Glacier variations, when correlated with changes in climate, show a close correspondence for more than 100 years of observation. Since the mid-1990s, in ...